Development of Media Based on Mobile Learning Materials of Basketball Basic Techniques - Hafida Hedi Warda; Febrita Paulina Heynoek; Rama Kurniawan (Universitas PGRI Palembang, 2023)
The development of learning media by utilizing technological developments can improve learning and the delivery of information. This study aims to develop and produce an iSpring suite application product that contains basic basketball techniques for students of the Department of Physical Education, Health and Recreation, Faculty of Sports Science, State University of Malang. This development method uses Research and Development by Lee & Own (2004) with five stages, namely 1) analysis, 2) design, 3) development, 4) implementation and 5) evaluation. Based on the results of the study of data from basketball experts, the percentage was 96%, learning experts were 90.4%, media experts were 98.2%, and involved 40 students of the PJKR Department. The distribution of small group trials was carried out on students of the 2020 PJKR Department, totaling 10 respondents with 2 male students and 8 female students. For the large group trial, there were 30 respondents with 12 male students and 18 female students. The trial results obtained 90% small group and 91% large group. Based on these data, it can be concluded that the product development of learning materials for basic basketball techniques based on this application is very valid and suitable for use by students of the PJKR FIK UM Department